2018
DOI: 10.3390/jfmk4010003
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Predict Falls in Older Adults Living in Nursing Homes: A Pilot Study

Abstract: Background: In community-dwelling older adults, slow gait speed is linked to falls; however, little is known about the use of gait speed to predict falls in nursing home residents. The prevalence of risk factors for falls in nursing home residents is multifactorial. Objective: The purpose of this study was to examine the relationship between falls and multiple factors such as age, sex, gait speed, mobility device, fear of falling, cognitive function, medication, and environmental causes in a nursing home setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…Estimating the risk of falling could provide guidance for adapting rehabilitation programs and provision of care. The occurrence of falls depends on extrinsic factors in the environment such as insufficient lighting or obstacles, for example, as well as intrinsic factors related to the physical capacities of the individual (Datta et al, 2018;Deandrea et al, 2013). Intrinsic precipitating causes have been associated with up to 80 % of falls recorded in institutionalized older people, with the highest prevalence amongst the oldest people (Bueno-Cavanillas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the risk of falling could provide guidance for adapting rehabilitation programs and provision of care. The occurrence of falls depends on extrinsic factors in the environment such as insufficient lighting or obstacles, for example, as well as intrinsic factors related to the physical capacities of the individual (Datta et al, 2018;Deandrea et al, 2013). Intrinsic precipitating causes have been associated with up to 80 % of falls recorded in institutionalized older people, with the highest prevalence amongst the oldest people (Bueno-Cavanillas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of residents prescribed psychiatric medications and urinary incontinence were top factors in the logistic regression, RF, SVM polynomial, SVM radial, and SVM sigmoid. Psychiatric medication was a very strong predictor of falls, consistent with previous research [6,7,9,10,[31][32][33], but inconsistent with a couple of studies [34,35]. The proportion of residents with urinary incontinence was an important factor in falls, supported in previous research [9][10][11][12], but not supported in other studies [7,32].…”
Section: Discussionmentioning
confidence: 44%
“…A study conducted in the USA concluded that 40.2% of elderly had experienced pre-institutionalization falls, 3 but that falls should also be seen as a consequence of institutionalization, given that they occur at a higher rate 4,5 and lead to more harmful consequences compared to elderly in the community. 1,5 Contributing factors to this increase in prevalence include greater dependence, chronic disease, the environment, cognitive decline and the presence of caregivers. 2,5,6 An unfamiliar environment and the presence of other people hinders risk identification and control, increasing the risk of a fall, particularly in the first few days of institutionalization, when one in five newlyadmitted elderly residents experiences a fall.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Contributing factors to this increase in prevalence include greater dependence, chronic disease, the environment, cognitive decline and the presence of caregivers. 2,5,6 An unfamiliar environment and the presence of other people hinders risk identification and control, increasing the risk of a fall, particularly in the first few days of institutionalization, when one in five newlyadmitted elderly residents experiences a fall. 3 It should also be noted that in the first few days of admission, the elderly may feel less confident performing daily living activities, which contributes to increased risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation